"Smart" gold nanoparticles for photoacoustic imaging: an imaging contrast agent responsive to the cancer microenvironment and signal amplification via pH-induced aggregation. Issue 53 (13th June 2016) - Song, Jaejung; Kim, Jeesu; Hwang, Sekyu; Jeon, Mansik; Jeong, Sanghwa; Kim, Chulhong; Kim, Sungjee
Abstract : pH-Responsive "smart" gold nanoparticles were demonstrated as a new photoacoustic imaging agent that can selectively respond to the cancer microenvironment and show the amplified signal in vivo . Abstract : 'Smart' gold nanoparticles can respond to mild acidic environments, rapidly form aggregates, and shift the absorption to red and near-infrared. They were used as a photoacoustic imaging agent responsive to the cancer microenvironment, and have demonstrated the cancer-specific accumulation at the cellular level and an amplified signal which is twice higher than the control in vivo .